A Significant Apparatus of Signs. Florentine Fifteenth Century and Construction of Sovereignty. Representations and Languages: Peer-reviewed article (Italian Review of Legal History, 2022)
Inspired by Riccardo Fubini’s researches and his interpretative and method proposal, original and often alternative to the recent historiographical debate on the Italian paths to state-building between the late Middle Ages and the early modern age, the essay elects the Florentine fifteenth century as a case study and traces its suggestive itinerary of the construction of sovereignty, not so much in the sense of praxis and concrete territorial government, but of a high form of legitimacy of power, capable of making Florence less indebted to the recognition of the two universal entities (sovereign for the Middle Ages) of Church and Empire. The Parliament of 1° September 1378, by declaring the “totalis, plenissima et integra auctoritas et potestas populi Florentini” and by qualifying the Statutory Councils as “liberi et soluti”, can rise to the genetic moment of the claim of a sovereignty that medieval jurisprudence had hitherto described as a not dominated position of power and, therefore, logically connected to the solutio a legibus. Moreover Florence, here like other potentie grosse, builds, in the crisis of the universalistic and communal medieval order, an important part of its sovereignty precisely through the maiestas and the connected crimen maiestatis, making use of interesting criminal strategies to conservation and growth of dominion, many of which in concert with the intellectual milieu of jurists. However, it is not only by usurping the forbidden attribute of majesty – forbidden because it is reserved by medieval jurisprudence only for the universal entities of the Church and Empire – and by repressing dissent with lese majesty that Florence satisfies its urgent need for legitimacy. Indeed, the majestic path remains perhaps the most karstic and the least striking, almost hidden among the arcana dominationis. Other signs were intended by ‘statesmen’ to publicly represent the sovereignty claimed by Florence within the same city and above all in the unprecedented external territorial projection, such as imperial diplomas, littera Florentina or Digesto Laurenziano, Leonardo Bruni’s Historiae Florentini and “scripture publice”. All those signs represented, in fifteenth-century Florence, “le cose sacratissime del popolo fiorentino”. The essay wants to offer a quick survey of it to give the reader another, premodern image of sovereignty. Once the itinerary has been traced, it will perhaps be possible to ask whether - beyond the specific case - the fifteenth-century time still has a lot to say, now that a singular Italian judicial matter which has been the subject of a recent study would seem to resurrect the ancient majestic vestiges, as if to mark the epiphany of a postmodern sovereign power with unusual features.
Keywords: Florentine Territorial State (sec. XV); sovereignty’s signs; juridical and political culture; maiestas; crimen laesae maiestatis